Fenomena Orang Tua Durhaka Dalam Al-Qur'ān: (Analisis Surah Luqmān ayat 15 Perspektif Ma’na Cum Maghza) - Lisa Asiati; Rama Rayhan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The phenomenon of unfilial parents in the current context is a response to the rampant violence, exploitation, and neglect of children that is prevalent today. Focusing on the interpretation of Q.S Luqmān verse 15 using the Ma'na Cum Maghza approach, this study emphasizes criticism of deviant parental behavior and moral value conflicts within the family. The method used is descriptive qualitative with library research analysis. The data was analyzed and obtained through three stages of Ma'na Cum Maghza, namely historical meaning (Ma'na Tarikhi), socio-historical message (Maghza Tarikhi), and phenomenal significance (Maghza Mutaharrik). The findings consist of three implications. First, there is a need to reexamine the concept of a child's obedience, whereby children are not required to obey their parents absolutely, but rather to obey the values of truth. Second, the dynamic significance of the phenomenon of disobedient parents is a criticism of the culture of parental authority as something that is indisputable. Third, this verse reinforces the value of reciprocity in family relationships. These findings are important for balancing family relationships in Islamic teachings.